Parental Health Attitudes and knowledge Factors Associated with Body Mass Index among Pakistani School-Aged Adolescents - Moazzam Tanveer, Umar Tanveer, Nayab Tanveer, Nadeem Roy, Asifa Zeba, Fouzia Abdul Razzaq, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the most recent estimates of underweight, overweight, and obesity prevalence in Pakistani school-aged adolescents aged 12 to 17 years and association with parental attitudes and knowledge factors. Methods: A cross-sectional study was conducted using a convenience sampling approach with 1,936 Pakistani from 42 schools in central Punjab province. The CDC US 2000 was used to define underweight < 5th percentile, overweight 85th ≤ BMI <95th percentile, and obese 95th percentile ≤ BMI, the Chi-square test was used. The Pearson correlation coefficient (r) was used to determine the correlation. The statistical significance level was set at p < 0.05. Results: prevalence of underweight U/W, overweight O/W, and obesity O/B was (24.5%, 4.6%, and 7.0%, respectively. The BMI had a positive relationship with gender, residency school kind and school level. Conclusion: Underweight, overweight, and obesity were prevalent among Pakistani school-aged adolescents. Some parents graded their children in an unreasonable manner. It is recommended that additional research be done to assess and enhance parents' understanding, attitudes, and behaviors regarding their children's weight. Keywords: Body Mass Index, School-aged adolescents, Parental health attitudes, Knowledge